2021
DOI: 10.1111/ijcp.14950
|View full text |Cite
|
Sign up to set email alerts
|

Gilaburu extract ( Viburnum opulus Linnaeus) is as effective as Tamsulosin in medical expulsive therapy of distal ureteral calculi

Abstract: Background To compare the extract of Gilaburu (Viburnum opulus Linnaeus) and Tamsulosin as a medical expulsive therapy (MET) in patients with distal ureteral calculi of 10 mm or less. Methods Data of 86 patients were prospectively collected. The patients were divided into two groups. In the first group, Viburnum opulus 1000 mg peroral 3 × 2 and diclofenac 50 mg peroral on‐demand (n = 43), in the second group Tamsulosin 0.4 mg peroral 1 × 1 and diclofenac 50 mg peroral on‐demand (n = 43) was given for MET in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(48 reference statements)
1
1
0
Order By: Relevance
“…The method considered beneficial is discovered to have an adverse impact on patient health. The findings are supported by various studies, such as those presented by Abdel Rahim et al and Gok et al, in which the researchers concluded the spontaneous passing method causes complications among patients 18,19 . MET is therefore considered effective in the clinical treatment of patients, specifically in the case of ureteral stones, as it initiates the process of passing stones, which commonly takes 6 weeks following the onset of symptoms.…”
Section: Discussionsupporting
confidence: 74%
“…The method considered beneficial is discovered to have an adverse impact on patient health. The findings are supported by various studies, such as those presented by Abdel Rahim et al and Gok et al, in which the researchers concluded the spontaneous passing method causes complications among patients 18,19 . MET is therefore considered effective in the clinical treatment of patients, specifically in the case of ureteral stones, as it initiates the process of passing stones, which commonly takes 6 weeks following the onset of symptoms.…”
Section: Discussionsupporting
confidence: 74%
“…V. opulus fruit contains high amounts of polyphenols [6] , phenolic acids [7] , flavonoids and anthocyanins [8] . The health benefits have been proven in studies thanks to its rich content of bioactive substances [9] , [10] , [11] , [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%